Transparent Contracting in the Colombian state (2014)
Contracting activity of the Colombian Government mainly seeks to satisfy the public interest, civilian needs, according to what is set forth in the Constitution of Colombia of 1999 in Article 400, within its main purpose is to guarantee the processes carried out in the governmental entities are made under equality and transparency, so that, the selected offer would be the most suitable, according to the kind of process. In case of processes for Resources Administration, the government has implemented progressively tools that allow to control and follow up of each step in the contracting prices, in which it is possible to identify in advance to the award some failures that may arise during process, as it is freely available on internet for a vast majority of the population and reporting processes and conditions under which the terms for any bidder oversight created or entity that can make the point with the contracting entity.